2005
DOI: 10.1096/fj.05-3875com
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 inhibits rat and human breast cancer cell proliferation: mutual cross inhibition with indoleamine 2,3‐dioxygenase

Abstract: Heme oxygenase-1 (HO-1) is the rate limiting enzyme of heme catabolism whereas indoleamine 2,3 dioxygenase (IDO) catabolizes tryptophan through the kynurenine pathway. We analyzed the expression and biological effects of these enzymes in rat and human breast cancer cell lines. We show that rat (NMU and 13762) but not human cells (MCF-7 and T47D) express HO-1. When overexpressed, we found this enzyme to have anti-proliferative and proapoptotic effects by antioxidant mechanisms in these four cell lines. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
120
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 60 publications
13
120
1
Order By: Relevance
“…However, HMOX-1 can induce cancer cell apoptosis and inhibit tumor cell motility. 30,31 Recently, HMOX-1 expression was shown to be elevated by PL in breast cancer cells and a determining factor in the differential response of normal breast cells to PL. 32 Interestingly, PL silenced ATP-binding cassette subfamily B, member 10 (ABCB10) expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, HMOX-1 can induce cancer cell apoptosis and inhibit tumor cell motility. 30,31 Recently, HMOX-1 expression was shown to be elevated by PL in breast cancer cells and a determining factor in the differential response of normal breast cells to PL. 32 Interestingly, PL silenced ATP-binding cassette subfamily B, member 10 (ABCB10) expression.…”
Section: Discussionmentioning
confidence: 99%
“…Because inhibition of NO production can ameliorate CIA depending on the time and route of delivery (36), it can be speculated that NO-IDO interactions limit the activation of IDO in the course of CIA. Similarly, HO-1-dependent generation of antioxidant compounds and consumption of the heme group can inhibit the activation of IDO, while inhibition of HO-1 has therapeutic effects in CIA (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intracellular ROS level was detected in tumors, and stimulation of the proliferation and invasion of tumor cells with inducing MMP-9 activation by ROS has been identified (19,20). HO-1 induction has been reported to reduce intracellular ROS level (14,16,21). Our previous study indicated that HO-1 induction protected macrophages and glioma cells from hydrogen peroxide -induced apoptosis (14,21).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of the HO-1 protein has been reported to protect against a variety of stress conditions such as hydrogen peroxide, cisplatin, UV irradiation, and inflammatory cytokine-mediated cell damage (12 -15). HO-1 has also been shown to inhibit the proliferation and induce apoptosis in several cancer cells such as breast carcinoma cells (16). Induction of HO-1 by the chemopreventive agent sulforaphane contributes to suppression of tumor cell growth by increasing the antioxidant response genes of hepatoma and breast cancer cells (17,18).…”
Section: Introductionmentioning
confidence: 99%